Detection of Human Immunodeficiency Virus Type 1 Antiretroviral Resistance Mutations by High-Density DNA Probe Arrays - Gonzalez, R. (American Society for Microbiology, 2004)
Genotypic resistance testing has become an important tool in the clinical management of patients infected with human immunodeficiency virus type 1 (HIV-1). Standard sequencing methodology and hybridization-based technology are the two principal methods used for HIV-1 genotyping. This report describes an evaluation of a new hybridization-based HIV-1 genotypic test of 99 clinical samples from patients infected mostly with HIV-1 subtype B and receiving treatment. This test combines RNA extraction with magnetic silica particles, amplification by nested reverse transcriptase PCR, and detection with high-density probe arrays designed to detect 204 antiretroviral resistance mutations simultaneously in Gag cleavage sites, protease, reverse transcriptase, integrase, and gp41. The nested reverse transcriptase PCR success rates at viral loads exceeding 1,000 copies/ml were 98% for the 2.1-kb amplicon that covers the Gag cleavage sites and the protease and reverse transcriptase genes, 92% for the gp41 amplicon, and 100% for the integrase amplicon. We analyzed 4,465 relevant codons with the HIV-1 DNA chip genotyping assay and the classic sequence-based method. Key resistance mutations in protease and reverse transcriptase were identified correctly 95 and 92% of the time, respectively. This test should be a valuable alternative to the standard sequence-based system for HIV-1 drug resistance monitoring and a useful diagnostic tool for simultaneous multiple genetic analyses.